From Confucianism to Nationalism - Trong Duong Tran (Asian Studies, 2020)
This paper examines how political discourses have changed as scholars seek answers regarding the origins of the Vietnamese people. The origin(s) of the Vietnamese people has long been a subject of debate. Confucian scholars from the fifteenth to the nineteenth centuries claimed themself to be descendants of Han people, the successors of the Han civilization. The colonial scholars (from 1860 to 1945), when using the theory of race, anthropology, and social evolution theory, thought that the Annam people were a hybrid breed, still in the process of evolution, and needed to be enlightened civilized. Indigenous scholars combined the Han ideology of Confucianism and the ideology of the French to claim that the Vietnamese were the descendants of the Hùng Vương. This ideological transformation was aimed at calling for patriotism, fighting against the French, and defending the nation from colonial domination. The results reveal that the process of changing paradigms in Confucian thought through colonialism led to the formation of fictive kinship and the spread of nationalism in Vietnam.